Enhancing the Competitiveness of Local Ponorogo Coffee Through Value Chain Analysis from an Islamic Economics Perspective - Sadda Salma Alsyaroza; Muchtim Humaidi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: The coffee sector in Ponorogo Regency, East Java, is experiencing growth, marked by the increase in coffee shops and food stalls. However, local farmers' coffee production has not been fully absorbed by market players, indicating an imbalance in production and marketing. Geographically, Ponorogo holds significant potential for coffee development, particularly on the slopes of the Wilis Mountains, with its favorable altitude and fertile soil. This study aims to analyze the value chain and competitiveness of Ponorogo coffee by integrating the concept of maslahah (benefit) into Islamic economics. Research Methods: This research employs a qualitative method with a case study approach. Data were obtained through observation, documentation, and interviews at each stage of the coffee value chain, including coffee farmers (upstream), coffee business owners (downstream), and the Agriculture Office (Plantation Office) in Ponorogo Regency.The case study approach was used to understand the factors within the value chain that influence the competitiveness of local Ponorogo coffee and the integrated strategies for achieving shared and sustainable benefits. Results: The research results show that Ponorogo coffee's competitiveness remains relatively weak due to factors within the value chain that are not optimally integrated from upstream to downstream. Constraints in the Ponorogo coffee value chain include long harvest periods, weather constraints, technological limitations, suboptimal picking practices, low-value-added processing, and limited market access and minimal uptake of local Ponorogo coffee downstream. Conclusion: Therefore, an integrated development strategy is needed through strengthening farmer resources, modern technology, government support and synergy from various parties so that it can increase the competitiveness and welfare of farmers.